(untitled) (Journal of Information Technology and Digital World, 2022)
The purpose of the task is to construct a prototype of the Smart Power Extender and bridge the distance between the conventional and futuristic extension board. The proposed machine includes a microcontroller-primarily based improvement board that controls this prototype. Also, this prototype presents real-time tracking of the equipment’s utilization to a Backend Server that manages the Internet of Things (IoT). This prototype also includes different protection functions provided by app interface, allowing the equipment to run most straightforwardly for a selected time limit. These functions permit the consumer to govern and protect the home equipment linked to it everywhere around the sector with the Internet’s assistance.